2019
DOI: 10.1177/1744806919866529
|View full text |Cite
|
Sign up to set email alerts
|

The preemptive analgesia of pre-electroacupuncture in rats with formalin-induced acute inflammatory pain

Abstract: Background Electroacupuncture has been elicited to effectively alleviate the pain sensation. Preemptive analgesic effect of pre-electroacupuncture has also been suggested in recent studies, while the underlying analgesic mechanism of pre-electroacupuncture requires further investigation. This study aimed to explore the preemptive analgesia of pre-electroacupuncture in formalin-induced acute inflammatory pain model. Methods Forty rats were randomly divided into control, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…Electroacupuncture (EA) is one of the most common methods for treating pain in Chinese medical clinics and has a therapeutic effect on acute and chronic pain. 28,29 Previous studies have shown that EA can partly prevent the transition from acute to chronic pain. 30,31 However, the mechanisms underlying its preventive effect remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Electroacupuncture (EA) is one of the most common methods for treating pain in Chinese medical clinics and has a therapeutic effect on acute and chronic pain. 28,29 Previous studies have shown that EA can partly prevent the transition from acute to chronic pain. 30,31 However, the mechanisms underlying its preventive effect remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, various studies have proved the efficacy of EA in BCP from animal experiments and clinical trials ( Chen et al, 2008b ; Paley et al, 2011 ; Ryu et al, 2014 ; Paley et al, 2015 ). As reported, EA at ST36 acupoint counteracted cancer pain, attenuated nociceptive effects in inflammatory pain conditions and also neuropathic pain ( Zhang et al, 2012 ; Lu et al, 2018 ; Liu et al, 2019 ). Similar analgesic effects have also been observed in BL60 ( Chang et al, 2012 ; Liang et al, 2016 ).…”
Section: Discussionmentioning
confidence: 70%
“…In mice, the centrally administered aminoglycoside (neomycin > gentamicin > kanamycin) induced significant analgesia due to blocking N-type calcium channels and thus lowering the neuronal calcium availability [ 10 ]. In rats, injection of formalin into the plantar surface of right hind paw as a pain induction model has dramatically increased the level of ionized calcium-binding adapter molecule 1 as well as the proinflammatory cytokines (IL-6 and IFN-γ), and pain neurotransmitters [ 60 ]. Tilmicosin administration was also associated with calcium channel blockade [ 57 , 61 ].…”
Section: Discussionmentioning
confidence: 99%